Otimização de um misturador estático para a produção de biodiesel - Sant anna, Mikele Cândida Sousa de (2012)
The computational fluid dynamics is a technique used for the analysis of fluid flow systems By this technique, it is possible to simulate new geometries of equipments as well as optimize one in use. In this research, we propose the development of new configurations for static mixers. Is proposed 27 simulations were conducted in a 24 factorial planning with 3 central points and 8 axial points, varying the thickness and the depth of the groove and the distance between the grooves, in order to obtain the velocity gradient as response. One could obtain two optimal settings were obtained. Once the machining of the optimal geometry was difficult, modifications were proposed to facilitate the construction of the mixer. So 16 configurations were obtained and the simplest one was built to be coupled to an experimental test system. The simulated and the experimental values of the velocity gradient were compared. One set up two tubular reactor systems with and without the static mixer were built for the experiments to obtain biodiesel. In these experiments, a 23 factorial planning was done, varying alcohol:oil ratio, catalyst concentration and temperature. The static mixer presented the value of the velocity gradients of 2288.93s-1, being 4,01% lower than the value found in the (2384.61s-1). A comparison of the experiments showed that the utilization of the mixer increased the ester conversion. The equation obtained from the empirical model of conversion to ester (Y) had an adjustment coefficient of 0.97 for the smooth tube reactor and 0.94 for the reactor with mixer.